2018
DOI: 10.1007/s12551-018-0432-5
|View full text |Cite
|
Sign up to set email alerts
|

Anderson-Fabry disease in heart failure

Abstract: Anderson-Fabry disease is an X-linked lysosomal storage disorder caused by mutations in the GLA gene that result in deficiency of the enzyme alpha-galactosidase A. The worldwide incidence of Fabry’s disease is reported to be in the range of 1 in 40,000–117,000, although this value may be a significant underestimate given under recognition of symptoms and delayed or missed diagnosis. Deficiency in alpha-galactosidase A causes an accumulation of neutral glycosphingolipids such as globotriaosylceramide (Gb3) in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 132 publications
(177 reference statements)
0
37
0
1
Order By: Relevance
“…In patients with HCM caused by rare storage disorders (e.g. Anderson–Fabry, Danon and Pompe diseases), HF most commonly takes the HFpEF phenotype due to an extensive, concentric increase in LV wall thickness . The increased wall thickness is caused partly by myocyte hypertrophy (due to lysosomal accumulation of glycosphingolipids), and partly by interstitial fibrosis stimulated by overproduction of profibrotic cytokines .…”
Section: Heart Failure In Hypertrophic Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with HCM caused by rare storage disorders (e.g. Anderson–Fabry, Danon and Pompe diseases), HF most commonly takes the HFpEF phenotype due to an extensive, concentric increase in LV wall thickness . The increased wall thickness is caused partly by myocyte hypertrophy (due to lysosomal accumulation of glycosphingolipids), and partly by interstitial fibrosis stimulated by overproduction of profibrotic cytokines .…”
Section: Heart Failure In Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Anderson–Fabry, Danon and Pompe diseases), HF most commonly takes the HFpEF phenotype due to an extensive, concentric increase in LV wall thickness . The increased wall thickness is caused partly by myocyte hypertrophy (due to lysosomal accumulation of glycosphingolipids), and partly by interstitial fibrosis stimulated by overproduction of profibrotic cytokines . Asymmetric LV hypertrophy in storage disorders is rare (< 2.5%), while biventricular hypertrophy may occur in up to 25% of patients .…”
Section: Heart Failure In Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…CRT has been proven to be useful for reducing ventricular dyssynchrony, decreasing filling pressures, and reversing remodeling, which result in reduced volumes and improvement in LV systolic function. [39][40][41] Biering-Sørensen et al 42 conducted a study on 3445 patients with HF and preserved EF, and they reported MD in 12% of the patients. However, MD did not predict poor outcomes.…”
Section: F I G U R Ementioning
confidence: 99%
“…Please find supplementary file(s); http://dx.doi.org/10.1253/circj.CJ-19-0127 T he enzyme α-galactosidase A is insufficient in Fabry disease, which causes an accumulation of neutral glycosphingolipids in various tissues. 1 We recently had the opportunity to examine endomyocardial biopsy and/or autopsy specimens from 3 patients with Fabry disease before and after enzyme replacement therapy (ERT). Supplementary Table lists the patient profiles.…”
Section: Supplementary Filesmentioning
confidence: 99%